EFFECT OF VITAMIN E AND VITAMIN C ON GROWTH AND BIOCHEMICAL COMPOSITION OF JUVENILE COBIA (Rachycentron canadum, Linnaeus 1766) - Anh, Pham Thi; Hung, Lai Van (Vietnam Journal of Marine Science and Technology, 2012)
Effect of vitamin E and vitamin C on growth and biochemical composition of juvenile cobia was carried out four weeks. The average weigh of fish when experiments started was 2.94g ± 0.5g and they were fed twice daily. Nine experiments have been carried out: 100C:30E; 200C:30E; 300C:30E; 100C:40E; 200C:40E; 300C:40E; 100C:50E; 200C:50E, 300C:50E and (-E-C) with three tank replicates (12 fishes  per tank). As a result, vitamin E and vitamin C clearly affected on the growth but not on biochemical composition of cobia. The highest growth (SGR, WG) and survival rate (S %), feed conversion ratio (FCR), feed intake (FI) were achieved on 300C:40E with survival rate: 100%. The growth rate of the fish was low in the treatment 100C:30E  and treatment without vitamin supplementation. At same level of vitamin E, the higher vitamin C supplementation, the higher survival rate attained.